PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR WALIKOTA TANGERANG SELATAN - Amelinda, Julia; Sartika, Dewi (Journal of Research and Publication Innovation, 2024)
This research aims to find out how work discipline and the work environment influence employee performance at the South Tangerang Mayor's Office, both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance with the regression equation Y= 7.821+0.787 X1, the correlation coefficient value is 0.771. The coefficient of determination value was 59.4% and the hypothesis test obtained t count > t table or (9.218 > 2.001). The work environment has a significant effect on employee performance with the regression equation Y= 5.730+0.876 X2. The correlation coefficient value is 0.757. The coefficient of determination value was 57.3% and the hypothesis test obtained t count > t table or (8.819 > 2.001). Work discipline and work environment simultaneously have a significant effect on employee performance